SBS/OKS ve YGS/ÖSS Sorularındaki Görecelik: "Hangi Yanıt Doğru: Benimki Mi, ÖSYM'ninki Mi?" - (:unkn) unknown (My University, 2017)
İyi bir lise ile üniversite eğitimi almak isteyenlerin yolu merkezi seçme sınavlarından geçmek zorundadır. Bu sınavlarda soruların test sorularından bir bölümü diğer test sorularına göre daha da bir zordur. Uzmanların "en doğru cevap isteyen" test soruları adını verdikleri soru tipinde bütün şıklar doğrudur ama biri ise daha doğrudur. Böylesi soruların soru kökü "en çok, en az, en etkili, en doğru, daha fazla, daha doğru" gibi nitelemelerle bitmektedir. Böylesi sorular hangi şıkkın doğru olduğuna dair çok önemli itirazları da beraberinde getirmekte, uygunluğu medya ve akademi çevrelerinde tartışılmaktadır. Nitel araştırma yöntemi çerçevesinde şekillenen araştırma, örnek olay desenine sahiptir. Bu çerçevede bu araştırmanın amacı, merkezi sınavlarda sorulan böylesi soruların oranını saptamak ve öğretmen adaylarının bu tip sorularla ilgili görüşlerini almaktır. Veri toplama araçları olarak doküman inceleme ile açık uçlu sorulardan oluşan anket kullanılmıştır. Son 15 yıl içerisinde gerçekleştirilen SBS/OKS ve YGS/ÖSS'deki "en doğru cevap isteyen" test soruları saptanmıştır. Ardından araştırmanın çalışma grubunu oluşturan 70 son sınıf Sosyal Bilgiler öğretmen adayına, araştırmacılarca seçilen 12 test sorusu sorulmuştur. Yanıtlamalarının ardından da açık uçlu sorulardan oluşan anket katılımcılarca doldurulmuştur. Nitel verilere uygulanan içerik analizi, merkezi sınavlarda sorulan bu tip soruların ortalama % 4-12 oranında olduğunu ortaya koymuştur. Yine bu sorulara verilen yanıt noktasında Sosyal Bilgiler öğretmen adayları oldukça zorlandıklarını ifade etmişlerdir.

In order to find a place in high schools which take position upper in the league table or to enter at well known universities students need to get high scores from the national examinations organized by the state in Turkey. In these exams difficulty level of questions is arranged as high so as to be distinctive in nature. An example of such questions can be those "what is the best answer below?". In this kind of questions, which ask "the most, the least, the effective, much more", nearly all choices are correct, but one is more correct than the others. In other word, it is the best explanatory choice as compared to the other choices. Thus, students are required to choice the best fits or the most correct alternative among already suitable or correct ones. There are cases where the correct answer announced by the government does not the "most, better" alternative. Therefore the present study aims to investigate the ratio of such questions in national exams and the social studies prospective teachers' opinions about such questions. Case study design among qualitative research tradition was adopted in this research. Questionnaire composed of open ended questions, which ask the prospective teachers' opinions about type, nature and efficiency of "the most..." questions, formed the main data collection tool. The central examinations of SBS/OKS and YGS/ÖSS conducted for last 15 years were examined so as to find out the ratio/percentage of such questions asked. Then, twelve questions among those which require the most correct answer were selected. They were compiled as a test and distributed to the social studies prospective teachers (n= 70) to answer. At completion of answering the questions, the prospective teachers' answers to and ideas about the nature of questions were obtained. The prospective teachers' open ended responses were analyzed via content analyses method. The results of the analysis indicated that "the most correct" questions formed 4-12 % of the questions asked in the national exams. Findings of the study showed that the prospective teachers had difficulty in finding the correct answer to such questions.
Relativity In SBS/OKS and YGS/ÖSS Questions and Answers: Which Answer Is Correct: Mine or ÖSYM's?
Keywords: Eğitim, Eğitim Araştırmaları